Isolation and Cultivation of Hair Melanocytes - Amit Khanna; Vijay Konala; Ranjith Kumar Singari; Shreya Dhepe (Medical Science: Trends and Innovations Vol. 7, 2025)
Hair melanocytes have gained significant attention for their utility in research particularly in the cosmetic industry. Studies have highlighted their applications in pigmentation research and disease modeling, making them an indispensable tool for understanding melanin biosynthesis and disorders associated with pigmentation. A reliable protocol for isolating and culturing hair melanocytes ensures consistency in cell yield, viability, and functionality. Coating of plates with foetal bovine serum (FBS), the inclusion of selective trypsinization and the use of G418 further ensure the removal of contaminating cell types, enhancing culture purity. This methodology ensures a high yield and >90% pure population of melanocytes.